Infrared light sensing performance of CdO-doped TiO2 thin films - Ilhan, Mustafa; Gorunmez Gungor, Zohre; Koc, Mumin Mehmet; Coskun, Burhan; Yakuphanoğlu, Fahrettin (Springer, 2023)
CdO-based materials are often used in infrared (IR) sensing devices. Previously, IR sensing properties of different CdO-based materials were reported. In this study, we produced CdO-doped TiO2 films and assessed their IR sensing capabilities. TiO2 solutions and CdO-doped TiO2 solutions were manufactured using sol-gel synthesis. Doping the TiO2 solutions with CdO allows us to tune the optoelectronic and photodiode characteristics of thin films in composite form. Pure TiO2 and CdO-doped TiO2 nanocomposite thin films were fabricated by spin coating p-Si wafers with gel solutions; pure TiO2 gel solutions; and 1%, 2%, and 10% CdO-doped TiO2 gel solutions. In the evaluation of the infrared (IR) light sensing performance of the thin films, both I-V and I-tIR performances of Al/n-Si/Ti1-xO2CdxO/Al thin films were addressed. Using I-V and I-t data obtained from under dark and IR illuminations, various IR sensitivity-related characteristics such as barrier height, photoresponsivity, photosensitivity, LDR (Light Dependent Resistor) values, and so on were analysed. These results were then compared with previous studies assessing the IR and light sensitivity characteristics of different types of thin films.
Keywords: Optical-Properties; Photodiodes; Parameters; Layer; Si